LEARNING ENGLISH THROUGH POETRY FOR EFL STUDENTS - I.G.A. Lokita Purnamika Utami (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Poetry can help students become more sensitive to language. However, in an EFL situation students may object to learning poetry. Thus, English teacher should know how to use poetry in their teaching. The teacher should also let the EFLlearners not feel worry about understanding poetry because not all poems are difficult. Moreover, what matter most is learning English through poem and not to learn about the poem itself. In short, it is suggested for EFL English teachers to have the learners explore some poems and write ones. Poetry gives abundant languageexposures that improve students’ language sensitivity and students’ creativity in using their English.